Optimization of mixotrophic marine microalga Tetraselmis sp. FTC208 cultivation in stirred tank photobioreactor - Mohamed, Mohd Shamzi (2014)
Microalgal lipid is gaining a reputation as the third generation renewable biofuel. Harnessing of efficient strains that can produce considerable neutral lipid in open systems are the interest of many researchers. Major hindrance lies in low biomass yield of photoautotrophic farming. The possibility to increase biomass and lipid productivity of local microalga isolate, Tetraselmis sp. FTC208, was assessed under photoautotrophic, mixotrophic and heterotrophic cultivation conditions. Four non-linear growth models (logistic, logistic with lag, modified Gompertz and Baranyi-Roberts) were assessed for the predictive ability of microalgal culture performance under different trophic conditions, followed by medium optimization using statistical methods (response surface methodology (RSM) and artificial neural network (ANN)) to enrich the nutrients of W-30 medium. The effect of hydrodynamic due to agitation on Tetraselmis growth was initially investigated in a 2 L stirred tank photobioreactor (ST-PBR) fitted with dual Rushton turbines. The prospect of improving the existing agitation system in 10 L ST-PBR was then explored by conducting a non-biological, stirred tank -specific preliminary mixing performance modelling to design the triple-impeller system for handling shear sensitive cells. The potential impellers tested include Rushton turbine (RT), Bakker‟s turbine (BT-6), A315 hydrofoil (HYD), and Narcissus turbine (NS). Attempt on up-scaling the cultivation of Tetraselmis sp. to 10 L ST-PBR was then made by taking into consideration the preferred hydrodynamics for microalga growth and mixing performance in 2 L ST-PBR. Through 16S rDNA and phylogenetic analysis, Tetraselmis sp. FTC208 has the closest homology to Tetraselmis striata. Baranyi-Roberts model was statistically accepted for the estimation of microalga growth kinetics under different culture conditions. Walne‟s medium was redesigned with „biomass capacity‟ () of at least 100% fixed for all micronutrient elements, while a sequential increased of 10% were imposed on deficient macronutrients. New medium (W-30) achieved Xmax of 1.505 g dcw/L and Pmax of 376 mg lipid/L ( 25% w/w), representing 1.8 and 3.7-fold improvements relative to the original Walne‟s formulation. Cultivation in mixotrophic (with light) gave better biomass and lipid production over heterotrophic (without light) conditions. W-30 medium supplemented with 30 g/L glucose boosted microalga growth to 8.08 g dcw/L when compared to the strictly photoautotrophic run, which gave biomass and lipid productivity of 404 mg dcw/Lday and 90.9 mg lipid/Lday, respectively. A quadratic model of RSM and an ANN network with 10 hidden neurons produced comparable results, albeit ANN formulation was observed to give higher output response. Optimized formulation utilizing W-30 as basal medium was composed of added glucose (24.05 g/L), NaNO3 (4.70 g/L) and yeast extract (0.93 g/L) eventually produced Xmax of 12.38 g dcw/L, lipid yield per cell, Pmax/Xmax of 195.77 mg lipid/g dcw and productivity, Pr lipid of 173.11 mg lipid/Lday. For cultivation in 2 L ST-PBR, the steady state biomass concentration rose with increased agitation relative to the “just suspended” speed (Njs) of 150 rpm (tip speed 0.409 s-1) at gas velocity (Ug) fixed at 0.5 VVM. The highest Xmax (16.88 g dcw/L) and Prcell (928.95 mg dcw/Lday), in conjunction with lipid yield (227.10 mg lipid/g dcw) and productivity (213 mg lipid/Lday) were observed at 250 rpm (tip speed 0.681 s-1), which corresponded to Pg/V and kLa of 190.93 W/m3 and 0.0118 s-1, respectively. Based on the cultivation data of 2 L ST-PBR, the impeller tip speed (ND) at 0.681 m/s and kLa at 0.0118 s-1 were adapted in 10 L ST-PBR equipped with three Rushton turbines (RT) as well as another photobioreactor unit retrofitted with NS-BT6-NS. This triple impeller configuration was believed to impose moderate shear effect without risking the oxygen transfer rate to the medium. Scale-up criterion employing constant kLa in NS-BT6-NS system was found to exert better influence on microalgal growth over strategy that was based on equal tip speed. Highest Xmax was obtained at 18.07 g dcw/L with 22.6% w/w of lipid bodies. The fatty acid profile of lipid derived from the 10 L ST-PBR mixotrophic culture exhibited C16:0 (18.5%), C18:1n9c (15.7%), C18:0 (9.3%) and C18:3n6 (6.3%) in addition to an uncommon monounsaturated C12:1 (15.1%). Tetraselmis bio-oil merits a further investigation as feedstock for producing biodiesel since its saponification value (SV = 148.48), iodine value (IV = 104.38) and cetane number (CN = 59.57) all adhered to the range set by the established biofuel standards.